Synchronizing a collaborative arm’s digital twin in real-time - Nascimento, Felipe H. N.; Cardoso, Sabrina A.; Lima, Antonio M. N.; Santos, Danilo F. S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This paper proposes a real-time synchronization strategy that employs kinematic control to streamline the interaction between a digital twin and its physical counterpart, specifically focusing on a collaborative robotic arm. By exploiting the principles of kinematic control, we aim to harmonize the states of the cobot arm and its digital twin in real-time. This synchronization strategy incorporates the Robot Operating System (ROS) 2 and the Coppelia framework, emphasizing the advantages of ROS 2 Quality of Service (QoS) features for the efficient control of digital twins. Experiments are conducted to validate the algorithm’s efficacy and performance, providing empirical evidence of improved accuracy, security, and efficiency in the operation of digital twin robotic systems. This research contributes to the ongoing evolution of robotic system design, particularly in real-time monitoring, operation, and the integration of digital twins into manufacturing and other industrial processes.